Identifying distracted-driving events from on-road observations using a moving vehicle: A case study in New Jersey. (November 2022) - Sajid Hasan, Ahmed; Patel, Deep; Alfaris, Ruqaya; Jalayer, Mohammad
Highlights: "On-road Observations Using a Moving Vehicle" was employed to record distracted driving events. Cellphone use was the most prominent type of distraction. Summer had a higher rate of distractions than spring. Handheld phone use - phone to ear significantly increased during the weekdays. An increase in speed limit and shoulder width significantly increased the distractions. Abstract: Distracted driving is a major traffic safety concern in the USA. To observe and detect distracted-driving events, various methods (e.g., surveys, videos, and simulations) involving the collection of cross-sectional data from individual subjects have been used in the transportation field. In this study, we employed an unconventional approach of on-road observations using a moving vehicle to collect data on distracted-driving events for multiple subjects in New Jersey. A data-collection crew member continuously navigated selected corridors to record driver-distraction events. A GPS (Global Positioning System) tracker was used to timestamp and record the location of each incident. Two non-parametric tests (Mann–Whitney U test and Kruskal–Wallis test) were performed to identify the significance of the variations in distracted-driving behaviors due to changes in temporal variables (e.g., day of the week, season), the type of roadway, and the geometric properties of the roadway. The results indicated that cellphone use was the leading type of distraction. Additionally, "handheld phone use (phone to ear), " "fidgeting/grooming, " "drinking/eating/smoking, " and "talking to passengers" events were significantly affected by the time of day and the geometric properties of the roadway. The results of this study are expected to assist state and local agencies in promoting awareness of distracted driving with the aim of reducing the frequency and severity of distracted driving-related crashes.